Ginsenoside Rg3 Enhances Islet Cell Function and Attenuates Apoptosis in Mouse Islets - Kim, S. S.; Jang, H. J.; Oh, M. Y.; Eom, D. W.; Kang, K. S.; Kim, Y. J.; Lee, J. H.; Ham, J. Y.; Choi, S. Y.; Wee, Y. M.; Kim, Y. H.; Han, D. J. (ELSEVIER SCIENCE INC, 2014)
Background. The transplantation of isolated islets is thought to be an attractive approach for curative treatment of diabetes mellitus. Panax ginseng has been used in oriental countries for its pharmacologic effects, such as antidiabetic and antiinflammatory activities. 20(S)-ginsenoside Rg3 (Rg3), an active ingredient of ginseng saponins, has been reported to enhance insulin secretion-stimulating and antiapoptotic activities in pancreatic beta cells. We performed this study to examine the hypothesis that preoperative Rg3 administration can enhance islet cell function and antiapoptosis before islet transplantation. Methods. Balb/c mice were randomly divided into 2 groups according to the administration of Rg3 after islet isolation. Mouse islets were cultured in medium supplemented with or without Rg3. In vitro, islet viability and function were assessed. After treatment of islets with a cytokine cocktail (tumor necrosis factor alpha, interferon-gamma, and interleukin-1 beta), cell viability, function, and apoptosis were assessed. Results. Cell viability was similar between the 2 groups. Islets cultured in medium supplemented with Rg3 showed 2.3-fold higher glucose-induced insulin secretion than islets cultured in medium without Rg3. After treatment with a cytokine cocktail, glucose-induced insulin release, total insulin content of islets, and apoptosis were significantly improved in Rg3-treated islets compared with cytokine-treated islets. Cytokine-treated islets produced significantly higher levels of nitric oxide (NO) than islets treated with Rg3. Conclusions. These results suggest that preoperative Rg3 administration enhanced islet function before islet transplantation and attenuated both cytoldne-induced damage associated with NO production and apoptosis. Rg3 administration might be a prospective management to enhanced islet function and ameliorate early inflammation after transplantation.
Keywords: BETA-CELLS; TRANSPLANTATION